Effects of the Soluble Fiber Complex PolyGlycopleX® on Glucose Homeostasis and Body Weight in Young Zucker Diabetic Rats - Gahler, Roland J.; Grover, Gary J.; Reimer, Raylene A.; Wood, Simon (Frontiers in Pharmacology, 2011)
Dietary fiber can reduce insulin resistance, body weight and hyperlipidemia depending on fiber type, water solubility and viscosity. PolyGlycopleX® (PGX®) is a natural, novel water soluble, non-starch polysaccharide complex that with water forms a highly viscous gel compared to other naturally-occurring dietary fiber. We determined the effect of dietary PGX® vs cellulose and inulin on the early development of insulin resistance, body weight, hyperlipidemia, and glycemia-induced tissue damage in young Zucker diabetic rats (ZDFs) in fasted and nonfasted states. ZDFs (5 weeks old) were fed a diet containing 5% (wt/wt) cellulose, inulin, or PGX® for 8 weeks. Body weight, lipids, insulin and glucose levels were determined throughout the study and Homeostasis Model Assessment (HOMA) was used to measure insulin sensitivity throughout the study in fasted animals. At study termination, insulin sensitivity (oral glucose tolerance test, OGTT) and kidney, liver, and pancreatic histopathology were determined. Body weight and food intake were significantly reduced by PGX® vs inulin and cellulose. Serum insulin in fasted and non-fasted states was significantly reduced by PGX® as was non-fasted blood glucose. Insulin resistance, measured as a HOMA score, was significantly reduced by PGX® in weeks 5 through 8 as well as terminal OGTT scores in fed and fasted states. Serum total cholesterol was also significantly reduced by PGX®. PGX® significantly reduced histological kidney and hepatic damage in addition to reduced hepatic steatosis and cholestasis. A greater mass of pancreatic -cells was found in the PGX® group. PGX® therefore may be a useful dietary additive in the control of the development of the early development of the metabolic syndrome.